Comparison of circadian, weekly, and seasonal variations of electrical storms and single events of ventricular fibrillation in patients with Brugada syndrome. (June 2016) - Aizawa, Yoshiyasu; Takatsuki, Seiji; Kaneko, Yoshiaki; Noda, Takashi; Katsumata, Yoshinori; Nishiyama, Takahiko; Kimura, Takehiro; Nishiyama, Nobuhiro; Fukumoto, Kotaro; Niwano, Shinichi; Kurita, Takashi; Mitsuhashi, Takeshi; et al.
Abstract: In patients with Brugada syndrome (BS), VF occurred predominantly during the nocturnal period. Some patients also developed ESs. In addition to the circadian rhythm, patients showed weekly and seasonal patterns. The patients with ESs had peak episodes of VF on Saturday and in the winter and spring, while episodes of VF in patients with single VF events occurred most often on Monday with smaller seasonal variation. Except for age, there was no difference in the clinical or ECG characteristics between the patients with ESs and those with single VF episodes.